The Effect of Dividend Policy and Market to Book Value of Equity on Firm Value in Energy Sector Companies Listed on Indonesia Stock Exchange - Indriany Elisabeth Bataha; Ventje Ilat; Meily Yoke Betsy Kalalo (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of dividend policy and market to book value of equity on the value of energy sector companies listed on Indonesia Stock Exchange for the 2017–2021 period. This study uses quantitative method with purposive sampling as method of selecting samples and 30 companies were selected as samples. The analytical method used is a multiple linear regression. The results of this study indicate that partially dividend policy has a significant positive effect on firm value and market to book value of equity has a significant negative effect on firm value.